Assessing the operational efficiency of wastewater services whilst accounting for data uncertainty and service quality: a semi-parametric approach. Issue 7 (16th November 2020) - Ananda, Jayanath
ABSTRACT: Wastewater services involve complex technical and environmental processes. Conventional performance assessments often disregard the service quality aspects of the sector. This article applies an advanced semi-parametric modelling framework based on data envelopment analysis to measure the economic efficiency of wastewater service provision in Australia whilst accounting for service quality. We find that the volume and type of sewer treatment, the number of treatment plants, and population density are among the exogenous factors that influence the operational efficiency of wastewater utilities. Inclusion of service quality parameters can make a significant difference in efficiency evaluations.